Measures of corporate tax avoidance: empirical evidence from an emerging economy - Salihu, Ibrahim Aramide; Sheikh Obid, Siti Normala; Annuar, Hairul Azlan (Universiti Malaysia Sarawak, 2013)
The prevalence of tax avoidance practices has necessitated several efforts in understanding the determinants of the menace. While these efforts are highly commendable, the studies so far lack the proper construct for measuring the term ‘corporate tax avoidance’. This has posed some limitations to the interpretation of research findings in this respect. To this end, Hanlon and Heitzman (2010) proposed a measure for the conforming tax avoidance, which has not receivedany empirical investigation. The objective of this study, therefore, is to provide empirical evidence for or against the proposed measure. To achieve this objective, three established measures were compared with the proposed measure using the annual reports of the Malaysian top 100 companies based on FTSE tradable index. The results of the ANOVA and post hoc test show the proposed measure to be statistically and significantly different at 5%. The finding of the study is of great relevance for proper interpretation of research findings, especially within the context of the study.